Manajemen Sarana dan Prasarana Terhadap Keberlanjutan Fasilitas yang Mempengaruhi Proses Pembelajaran SMAN 1 Wonoayu - Rachel Hamdan Al Kahfi; Akhmad Wildan Nur Rahma Putra; Zhafira Amalia Nur Faizah; Yearlie Aurellia Salsabil; Ayu Wulandari (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
This research examines the management of facilities and infrastructure at SMA Negeri 1 Wonoayu, with the research focus being management of facilities and infrastructure affects the sustainability of facilities. The aim of this research is to gain an understanding of facilities and infrastructure management. This research uses a qualitative approach with a descriptive approach. The data source for this research comes from the manager of facilities and infrastructure, namely the Vice Principal Mr. M. Syamsul Arif, S.Pd., M.Si., collecting data through techniques such as observation and interviews. The research results show that the facilities and infrastructure at SMA Negeri 1 Wonoayu are used optimally by students and teachers. Students use the facilities to learn, and teachers deliver lessons using the tools available in the classroom. All facilities and infrastructure at SMA Negeri 1 Wonoayu have been maintained optimally, with routine checks, repairs and maintenance.